MEMUPUK TOLERANSI KAUM MUDA KATOLIK MELALUI DIALOG DAN VISITASI KE RUMAH IBADAHUMAT BERAGAMA LAIN DI RUTENG, MANGGARAI - Fransiska Widyawati (Randang Tana - Jurnal Pengabdian Masyarakat, 2021)
Intolerance is a worrying problem in Indonesia. Many of the perpetrators are young people. There are many root causes of intolerance. Some of these are the lack of knowledge about other religions and the absence of relationships with others. In order to prevent the young Catholics in Ruteng from being intolerant, this program offers them dialogue activities and visitations to non-Catholic places of worship. The main objectives are to increase knowledge and build good attitudes and character. Through the program, the youth can do dialogue with other religious leaders. With this activity, they can have tolerance and respect for other religious communities. The main methods of this activity are dialogue and field visitations. Communities that are dialogue partners of religious leaders and people from the Muslim, Hindu, three Protestant denominations, namely the Evangelical Christian Church in Timor (GMIT), the Indonesian Bethel Church - Reign of Christ King (GBI-ROCK) and the Indonesian Bethel Church - Hosana. Location of the dialogue and visitation activities in their respective houses of worship in Ruteng. The result was that after this activity, young Catholics gained new knowledge about other religions, got to know places of worship for other religions, and had a positive perspective on other religions. Therefore, dialogue and tolerance activities are very beneficial for Catholic youth in Ruteng and effectively foster religious tolerance. It is recommended that this activity be carried out regularly for other groups of young people and even for all communities